The Just Warrior Ethos: A Response to Colonel Riza. Issue 3 (2nd July 2016) - Chapa, Joseph O.; Blair, David J.
ABSTRACT: In 2014, Colonel M. Shane Riza published an article in this journal arguing that remotely piloted aircraft (RPA) and robotic weapons threaten the US Air Force's warrior ethos. Riza has clearly articulated the sentiments of one side of a vibrant debate within our service. This paper presents an alternative view; a view held by some who have experienced these new forms and tools of war, and who have wrestled with their implications first-hand. In this paper, we address some methodological concerns with Riza's approach and then engage some misunderstandings about RPA's relationship to military history and to risk. The second part of this paper takes a close look at some of the early Just War thinkers to determine what implications the tradition may have on the warrior ethos. We propose, as an alternative to Riza's position, a return to an ethos grounded in humility, charity, and a conception of war as a last resort; in short, a return to the Just Warrior Ethos.